Local governance and renewable energy projects: Local impact perception - Meireles, M.; Lima, F.; Robaina, M.; Villar, J.; Madaleno, M.; Dias, M.; Botelho, A.; Varum, C.; Roebeling, P.; Ramalho, E.; López-Maciel, M.; Oliveira, A. (Proceedings of the 6th International Conference on Energy and Environment (ICEE 2024), 2024)
Renewable energy sources (RES) projects play a crucial role in transitioning away from fossil fuel-based energy production and use, and Portugal is at the forefront of renewable-based electricity generation, at European Union level. Social acceptance and impact perception of RES projects have been focused on overall or affected populations, often disregarding other stakeholders, such as local municipalities. The present study addresses this gap in the case of Portugal. Central Region was chosen due to its relevance in the national energy sector and its potential to make a positive contribution to Europe's energy efficiency and RES commitments. Namely, 70% of its final electricity consumption is based on renewable generation, while the national average is 59.1%. For this purpose, a series of semi-structured interviews have been developed for the top 10 municipalities with the highest presence of RES projects, located in the Central Region of Portugal. The survey was designed based on existing literature regarding social acceptance and attitudes towards RES. Expected results should emphasize, among socio-economic and environmental aspects, which are the main benefits or barriers towards project acceptance or rejection, from a municipality perspective.